Low expression of microRNA-328 can predict sepsis and alleviate sepsis-induced cardiac dysfunction and inflammatory response - Sun, Bin (Braz J Med Biol Res, 2020)
Sepsis often leads to cardiac dysfunction and inflammation. This study investigated the clinical value of microRNA-328 (miR-328) in sepsis and its role in cardiac dysfunction and inflammation caused by sepsis. The expression level of miR-328 in the serum of the subjects was detected by qRT-PCR. Receiver operating characteristic (ROC) curve measured the diagnostic value of miR-328 in sepsis. Rat sepsis model was established to detect left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP), and maximal rate of increase/decrease of left ventricular pressure (±dp/dt(max)). Myocardial injury markers serum cardiac troponin I (cTnI), myocardial kinase isoenzyme (CK-MB), and inflammatory factors were detected by enzyme-linked immunosorbent assay (ELISA). miR-328 expression was assessed in serum of sepsis patients and in rat models of sepsis. The AUC of ROC curve was 0.926, sensitivity 87.60%, and specificity 86.36%. Compared with the sham group, LVSP and +dp/dt(max) were decreased in the rat model of sepsis. LVEDP, -dp/dt(max), cTnI, CK-MB, tumor necrosis factor-α, interleukin (IL)-6, and IL-1β were upregulated in the rat model of sepsis. The low expression of miR-328 reversed these indicators. miR-328 is a diagnostic marker for patients with sepsis, and decreasing the expression level of miR-328 can ameliorate cardiac dysfunction and cardiac inflammation in sepsis.